Poly(DL-lactic acid)/triblock PCL-PDMS-PCL copolymers: synthesis, characterization and demonstration of their cell growth effects in vitro - (:unkn) unknown (ELSEVIER SCI LTD, 2001)
This paper describes the copolymerization of DL-lactic acid (DLLA) and triblock polycaprolactone-poly(dimethylsiloxane)lactone (TEGOMER). The physical properties of poly(DL-lactic acid)/triblock PCL-PDMS-PCL (PDLLA/TEGOMER) copolymer were determined by IR, H-1 NMR and DSC. T-g values of copolymer decreased with increasing TEGOMER unit content. Degradation of PDLLA/ TEGOMER copolymer films was investigated in phosphate buffered saline at pH = 7.4 and at 37 degreesC. The copolymers degraded to half of their original molecular weight values in 40 days. The morphology of the films during degradation was examined by scanning electron microscopy (SEM). Cell growth experiments using Swiss 3T3 fibroblasts demonstrated that PDLLA/TEGOMER copolymer matrices allow the attachment and growth of cells. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: degradation; poly(DL-lactic acid); copolymer; cell growth; DEGRADATION; LACTIDE; TISSUE; TRANSPLANTATION; MICROSPHERES; GLYCOLIDE; LIVER